PENERAPAN TOTAL QUALITY MANAGEMENT PADA BANK TABUNGAN NEGARA SYARIAH CABANG KOTA MALANG - Fita Firdausiyah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
Total Quality Management (TQM) is an early introduction of shari`ah in financial institutions. One of the issues that arise in the financial management of the Shari'ah is a model of governance (management) used was the same as the conventional management of financial institutions in general. Therefore it is needed innovation in its management. Implementation of TQM on financial institution shari`ah is expected to increase performance and quality of the institution. Implementation of TQM on Shari'ah financial institution is emphasis on the process of continuous improvement to uphold the values ​​of Shari'ah. In this study, there are problems namely: 1) How are the concepts of Total Quality Management (TQM) on BTN Shari`ah Malang? 2) How is the application of Total Quality Management (TQM) on services in BTN Shari`ah Malang? This study belongs to the kind of empirical research that emphasizes on the practice field. The approach used is qualitative approach, namely an analyzer shaped description sentence according the results of the processing of data obtained from the results of observations made. The concept of Total Quality Management (TQM) in service in Malang Islamic BTN wear pattern concept prima (P.O.LA.PR.I.MA), i.e. the first, excellent service which is friendly, courteous and friendly and caring, proactive and responsively. Second, innovation is the initiative that does completion and oriented towards creating added value. Third, the exemplary, its means becomes an example in a well-behaved and true as well as motivating the application of cultural values. Fourth, the professionalism, that is competent and responsible and to work smart and completely. Fifth, integrity, discipline, consistent, honest and dedicated. Sixth, cooperation, sincere and open, mutual trust and respect. In practice, BTN Shari`ah Malang, especially in the implementation of TQM in the service is still not maximized. To get the maximal result, all need time with the evaluation and consultant then so better in realizing service in accordance with hope and needs of customers.